Design of Website-Based Online Training (Bootcamp) Testing Management System - Munawarah, Munawarah; Solihah, Ananda Mar'atus (LPPM Universitas KH. A. Wahab Hasbullah, 2023)
Millennials like today, there are many ways to make it easier for someone to do anything. Included in studying the field of information technology. If on the lecture bench it will be a little challenging in managing time when attending class, then one way to make it easier is to create a bootcamp. Bootcamp is the perfect solution for pursuing a career in information technology without a degree. The purpose of this research is to create a system that can be used to test participants in online training by conducting several stage exams. So that participants get validation in the form of a transcript of the value of the exam results if they have taken the exam. This website is designed using the codeigniter framework. Therefore, the authors would like to conduct a study on web-based bootcamp participant tester systems with the title â€œDesign Of Website-Based Online Training (Bootcamp) Testing Management Systemâ€.